Знахідка меча Х ст. біля Хортиці (до питання про похід князя Святослава "в пороги" 972 р.) - Остапенко, М.А.; Саричев, В.Д. (Археологія, 2016)
Простежено взаємозв’язок інформації археологічних та писемних джерел про обставини загибелі князя Святослава в районі дніпрових порогів в контексті сітуації, яка склалася в Київській Русі в 971—972 рр. Uniquely preserved and decorated sword of the 10th century was found in the course of the Dnipro River near the Khortytsia Island (Zaporizhzhya) in 2001. This artefact is undoubtedly directly connected with the swords, similar in type and period to those discovered during the Dniproges Expedition in 1928. All the findings were located near the strategic Kichkas crossing described in detail by Constantine Porphyrogenitus in the 10th century. The discovery of a large number of elite swords, in combination with other memorials of this period such as Voznesenovsk encampment fortifications, settlements, and cultic center at Khortytsia raises the issue of the value of this part of the route «from the Varangians to the Greeks» for the history of Rus. The combination of geographical, historical, and archаeological data highlights the issue of the death of prince Sviatoslav Igorovych in March 972 in «the rapids». A comparison of these data with evidence of Chronicles may help establishing the causes and course of the events of the last months of prince’s life. The available data allow the authors to form the hypothesis about the existence of the strategic center on the territory between the Kichkas crossing and the Island of Khortytsia in the 10th century.Its recovery was one of the priorities for Prince Sviatoslav after the cessation of the war with Byzantium. It was necessary to ensure the secure trade and smooth functioning of the route «from the Varangians to the Greeks». Such version allows resolving the conflicting interpretation of Sviatoslav’s «desperation» adopted by the historians in the 18th century yet, and also bringing us closer to understanding of possible economic causes of the campaign «to the rapids». The discoveries of swords and other artefacts allow the authors to speak about the circumstances and nature of the final battle of Prince’s troops. The assemblage of ancient antiquities of the 10th century discovered near Kichkas and Khortytsia is directly related to the genesis of Ancient Rus state. В 2001 г. в русле Днепра возле о. Хортица (г. Запорожье) был обнаружен уникальный по сохранности и отделке меч Х в. Указанный артефакт, безусловно, находиться в прямой связи с находками аналогичных по типу и времени мечей, совершенных во время работы Днепрогесовской экспедиции в 1928 году. Все они сконцентрированы близ стратегической Кичкасской переправы, детально описанной в Х в. Константином Багрянородным. Находка большого количества элитных мечей, в сочетании с другими памятниками этого периода – укреплениями Вознесеновского лагеря, поселениями, культовым центром на Хортице ставит вопрос о значении этого участка пути «из варяг в греки» для истории Руси. Сочетание географических, исторических и археологических данных актуализирует вопрос гибели в марте 972 года «в порогах» князя Святослава Игоревича. Сопоставление их со свидетельствами летописных источников, может содействовать установлению причин и хода событий последних месяцев жизни князя. Имеющиеся данные позволяют выдвинуть гипотезу о существовании в Х в. в районе Кичкасской переправы и острова Хортица, стратегического центра, восстановление контроля над которым было одной из первоочередных задач князя Святослава после прекращения войны с Византией. Это было необходимо для обеспечения безопасной торговли и беспрепятственного функционирования пути «из варяг в греки». Такая версия позволяет устранить противоречивую трактовку «безрассудства» Святослава, принятую историками еще в XVIII в. и приблизить нас к пониманию возможных экономических причин похода «в пороги». Находки мечей и других артефактов позволяют говорить об обстоятельствах и характере последней битвы его дружины. Комплекс древнерусских древностей Х в. обнаруженный близ Кичкаса и Хортицы имеет прямое отношение к генезису древнерусской державы.